Comparison of click auditory brainstem response and chirp auditory steady-state response thresholds in children. (September 2018) - Mourtzouchos, Konstantinos; Riga, Maria; Cebulla, Mario; Danielides, Vasilios; Naxakis, Stefanos
Abstract: Objectives: During the last twenty years, auditory steady-state responses (ASSRs) are being used as an alternative and adjunct to the auditory brainstem response (ABR) for threshold estimation. This study aims at comparing and finding correlations between air-conduction thresholds using the traditional click ABR and the relatively recently used chirp ASSR test methods, for a large pediatric population. Methods: One hundred and thirty children referred to our Clinic from Hospitals and Clinics of Western Greece ranging in age from 5 to 79 months (mean age = 32.7 ± 14.0 months) participated prospectively. Results: Strong and statistically significant correlations were found between the average of the 1000, 2000 and 4000 Hz chirp ASSR thresholds and click ABR thresholds (rs = .826, p < .001), and the average of the 2000 and 4000 Hz chirp ASSR and click ABR thresholds (rs = .824, p < .001). Additionally, there have been measurements for some children with hearing loss in the severe-to-profound range during the ASSR test, but no ABR at the upper limits of the equipment. Click ABR and chirp ASSR thresholds averaged at 2000 and 4000 Hz were within 20 dB in 90% of the ears tested. Conclusions: The results of this study support the inclusion of chirp ASSRs into the pediatric test battery and indicate that they may provide an essential adjunct to the click ABR, especially in the management of very young children with severe-to-profound hearing loss.